Sprogbrugsartikler i bilingvale ordbøger - med Munksgaards Dansk-spansk ordbog som eksempel - Gawinski, Birthe (Nordiske Studier i Leksikografi, 1997)
The new (October 1996) Danish-Spanish dictionary from Munksgaard has introduced a new phenomenon in bilingual, general dictionaries, namely app. 30 usage notes, dealing with expressions which would normally be placed under different entries. The usage notes are placed in blocs with a reference from the headword. In these usage notes you may find a list of expressions used when greeting each ether in Denmark and Spain respectively. You can leam about politeness; how to swear; how to praise or criticize each ether, how to ask for something and how to reject somebody or tell somebody off The usage notes have been included in the dictionary in order to make it easier for the user to find the general expressions in certain situations.